EVALUATION OF BLOCKING LAYERS SENSITIZED SOLAR CELLS OF NANOSTRUCTURED TITANIUM OXIDE - Nazario, Russell (2015)
In conventional Grätzel cells, the conductive substrate (FTO) on the electrode, a mesoporousTiO2 layer ~ um, prepared by the doctor blade method, with a heat treatment at 450 ° C,the dye-sensitized deposited (D7). In this article an additional TiO2 layer between the FTOand the electrode is added, because the electrode has a high porosity and don´t has a goodcontact with the FTO, so we suggested adding a compact layer that helps transfer electronof electrode to FTO and prevents direct contact between the FTO and electrolyte. Thuselectron recombination is prevented by the FTO hollow electrolyte. Subsequently certaincharacterizations are performed to determine the thickness of the block and to analyze themorphology of the electrode by Scanning Electron Microscopy. Finally the I-V curve waswe determined to analyze its efficiency with a radiation of 1000W/ m2 efficiency of 2,39%was reached.